2008
DOI: 10.1016/j.bmc.2008.03.023
|View full text |Cite
|
Sign up to set email alerts
|

An epoxidation mechanism of carbamazepine by CYP3A4

Abstract: Human CYP3A4 catalyzes the 10,11-epoxidation of carbamazepine (CBZ). However, the epoxide is less stable in terms of potential energy than hydroxides of the six-membered aromatic ring. To clarify the reason why CYP3A4 produces such an energetically unfavorable compound, the mechanism of epoxidation of CBZ by CYP3A4 was investigated by theoretical calculations. The reaction consisted of two elementary processes in which two C-O bonds were generated stepwise. The rate-determining step was the first one and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 74 publications
(90 reference statements)
1
16
0
Order By: Relevance
“…5B), and interacts with AA (Table 1). In the CYP3A4 carbamazepine epoxidation mechanism, F304 and A305 were located at the nearest position to the Fe atom and it is noted that they hold the substrate near the heme Fe atom for the reaction [40]. E321 of CYP4A22 is corresponding to A305 in CYP3A4.…”
Section: Discussionmentioning
confidence: 99%
“…5B), and interacts with AA (Table 1). In the CYP3A4 carbamazepine epoxidation mechanism, F304 and A305 were located at the nearest position to the Fe atom and it is noted that they hold the substrate near the heme Fe atom for the reaction [40]. E321 of CYP4A22 is corresponding to A305 in CYP3A4.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, theoretical computations can reveal metabolic mechanisms at the atomic and electronic levels. [19][20][21][22][23][24] In fact, Hoshino et al 20,23 demonstrated that molecular dynamics (MD) and density functional theory (DFT) calculations can 4 play a significant and indispensable role in the detailed understanding of CYP3A4-mediated metabolism of carbamazepine.…”
Section: Introductionmentioning
confidence: 99%
“…However, the recent advances in resolution of three-dimensional structures of many CYPs including CYP2C9 13,14 allowed the development of various computational approaches that are currently applied for quantitative prediction of pharmacokinetics, interaction between the enzyme and its substrates, and also redox partners. [15][16][17][18][19] Thus, molecular dynamic simulations and subsequent substrate-docking simulations have been performed to clarify the mechanisms of enzymatic activity decrease in the different allelic variants of CYP2C9. 20 Amino-acid substitutions in these proteins were found to increase the fluctuation of the residues responsible for the substrate holding and alteration of the substrate-binding pocket.…”
Section: Introductionmentioning
confidence: 99%